Peningkatan Kemampuan Menggambar Teknik Siswa SMK Menggunakan Software Berbasis Computer Aided Design (CAD) Sebagai Upaya Pengembangan Kualitas Nilai Sumber Daya Manusia (SDM) Untuk Menghadapi Dunia Kerja - Bisono, Rahayu Mekar; Hendarti, Devina Rosa (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
This program was held aimed at improving the competency of technical drawing of vocational students in the Municipality of Kediri. Competence in this service consists of three aspects, namely affective, cognitive, and psychomotor. This program is carried out with a model of meeting in the classroom, giving theory, practicum, performance of making parts with image models and real object models. The improvement of students' abilities was measured using observation sheets of student activities to determine the improvement of the affective aspects of students, the pretest and posttest instruments to determine the increase in cognitive aspects of students, the worksheets of students to determine the improvement of psychomotor aspects. The first output of this program is to increase the ability of vocational students in the field of mechanical engineering with the help of computers using CAD-based software. The next output is a competency certificate that will be given to students in accordance with their competencies.